EPID-01. THE EPIDEMIOLOGY OF BRAIN METASTASES IN ADOLESCENT AND YOUNG ADULT (AYA) PATIENTS DISTINCTLY DIFFERS FROM THE ADULT POPULATION. (12th November 2021) - Lamba, Nayan; Iorgulescu, Bryan
Abstract: INTRODUCTION: Few data exist regarding the epidemiology of brain metastases (BMs) in adolescent and young adult (AYA) patients. Herein we use national cancer registry data to dissect their epidemiology and compare to the adult population. METHODS: AYA patients (15 ≤ age ≤ 39) who newly presented with a BM between 2010 and 2017 were identified in the National Cancer Database (comprising >70% of all newly-diagnosed cancers in the U.S.). The epidemiology of BMs was analyzed by primary cancer of origin, and compared between AYA and adult patients. Overall survival was analyzed with multivariable Cox regression. RESULTS: 2, 773 AYA patients presenting with BMs were identified (98% with histopathological diagnosis), compared to 156, 103 adult patients (94% with histopathological diagnosis). Whereas 39.6% of newly-diagnosed brain tumors with histopathological confirmation were BMs in adults, BMs represented only 5.8% of such tumors in AYA patients. Additionally, the distributions of primary cancer types differed substantially between adults and AYA patients: notably, NSCLC dominated in adults (64.2%) vs representing only 31.6% of BMs in AYA patients. AYA patients were more likely to present with BMs from melanoma (13.0% of AYA BMs vs 3.7% in adult), soft tissue (4.5% vs 0.3%), testicular (in males 26.2% vs 0.1%), and breast (in females 29.5% vs 7.8%) primaries. Among breast BMs in females, AYA patients were less likely to have HR+/HER2- primaries (40.2% vs 47.8%) and more likely to have HER2+ (25.2% vs 20.1%) and triple positive (11.1% vs. 9.8%) primaries than adults. Overall survival was significantly longer for AYA patients with BMs (HR=0.61 compared to adult patients, 95%CI:0.58-0.64, p< 0.001) even after adjusting for primary cancer type, patient sex. CONCLUSIONS: The epidemiology and cancer types of BMs in AYA patients differ substantially from adult patients. Future research aimed at understanding the unique differences in pathophysiology and outcomes of BMs in AYA patients is warranted.